FPGA-Based CNN for Eye Detection in an Iris Recognition at a Distance System. - Ruiz-Beltrán, Camilo Andrés; Romero-Garces, Adrian; González-García, Martín; Marfil-Robles, Rebeca; Bandera-Rubio, Antonio Jesús (My University, 2023)
Neural networks are the state-of-the-art solution to image-processing tasks. Some of these neural networks are relatively simple, but the popular convolutional neural networks (CNNs) can consist of hundreds of layers. Unfortunately, the excellent recognition accuracy of CNNs comes at the cost of very high computational complexity, and one of the current challenges is managing the power, delay and physical size limitations of hardware solutions dedicated to accelerating their inference process. In this paper, we describe the embedding of an eye detection system on a Zynq XCZU4EV UltraScale+ multiprocessor system-on-chip (MPSoC).
Keywords: Iris (Anatomía) - Reconocimiento; Redes neuronales (Informática); Deep Learning Processor Unit (DPU); Eye detection; Convolutional neural networks; Multiprocessor system-on-chip (MPSoC)